The Impact of External Relationships on the Growth of Young Technology Companies - Chris Justus (Technology Innovation Management Review, 2011)
Most management teams in young technology companies are aware that their success may depend on strong relationships with external organizations. However, it may not be clear to them which types of relationships are most likely to impact their growth. This article describes the author’s recent research to examine the relationship between the number and diversity of business relationships and the revenue growth of young companies. By examining data collected from 80 technology firms, and the 1943 relationships they established over a two-year period, certain types of relationships were found to have measurable impacts on growth. The article focuses on the managerial implications of these findings, which include the importance of early funding, niche identification, and building relationships with large firms.